Response of Drainage Pattern and Basin Evolution to Tectonic and Climatic Changes Along the Dinarides-Hellenides Orogen - Gemignani, L.; Mittelbach, B. V.; Simon, D.; Rohrmann, A.; Grund, M. U.; Bernhardt, A.; Hippe, K.; Giese, J.; Handy, M. R. (Frontiers in Earth Science, 2022)
The junction of the Dinaric and Hellenic mountain belts hosts a trans-orogenic normal fault system (Shkoder-Peja Normal Fault, SPNF) that has accommodated oroclinal bending, as well as focused basin formation and drainage of the Drin River catchment. Analysis of fluvial morphology of this catchment reveals higher values of river slope indices (ksn) and χ (Chi) between the normal faults of the SPNF and the Drin drainage divide. The drainage divide is predicted to be migrating away from the SPNF, except at the NE end of the SPNF system. Two basins analysed in the hangingwall of the SPNF, the Western Kosovo Basin (WKB) and Tropoja Basin (TB), contain late Pliocene-to-Holocene sedimentary rocks deposited well after the main fault activity and immediately after the Last Glacial Maximum (LGM). These layers document an early Pleistocene transition from lacustrine to fluvial conditions that reflects a sudden change from internal to external drainage of paleo-lakes. In the TB, these layers were incised to form three generations of river terraces, interpreted to reflect episodic downstream incision during re-organisation of the paleo-Drin River drainage system. 36Cl-cosmogenic-nuclide depth-profile ages of the two youngest terraces (∼12, ∼8 ka) correlate with periods of wetter climate and increased sediment transport in post-LGM time. The incision rate (∼12 mm/yr) is significantly greater than reported in central and southern Albania. Thus, glacial/interglacial climatic variability, hinterland erosion and base-level changes appear to have regulated basin filling and excavation cycles when the rivers draining the WKB and TB became part of the river network emptying into the Adriatic Sea. These dramatic morphological changes occurred long after normal faulting and clockwise rotation on the SPNF initiated in late Oligocene-Miocene time. Faulting provided a structural and erosional template upon which climate-induced erosion in Holocene time effected reorganisation of the regional drainage pattern, including the formation and partial demise of lakes and basins. The arc of the main drainage divide around the SPNF deviates from the general coincidence of this divide with the NW-SE trend of the Dinaric-Hellenic mountain chain. This arc encompasses the morphological imprint left by roll-back subduction of the Adriatic slab beneath the northwestern Hellenides.